Study the Effect of Different Parameters on the Corrosion and Inhibition Rate for Copper in Saline Solutions - Abdul Kader, Huda Dhiaa (Nahrain University College of Engineering Journal, 2013)
The corrosion of copper in highly concentrations of NaCl in present and absence of sodium soccinate (SS), has been reported using weight loss, and potentiodynamic polarization measurements. NaCl solutions were studied at stagnant condition and different temperatures (35-55oC), constant temperature and different rotational velocity (400 – 1200 rpm). The maximum inhibition efficiency at 35oC and decrease with increasing temperature and rotational velocity. The inhibition efficiency of 0.006 M SS obtained by weight loss measurements is about 14%, increasing to about 65% in 5 M NaCl solution and about 6. 76 %, increasing about 64.13 % in 1M NaCl solution. The potentiodynamic polarization measurements showed that SS is a mixed type inhibitor. The inhibition mechanism involves adsorption of SS on the copper surface.